2003
DOI: 10.1093/toxsci/kfg233
|View full text |Cite
|
Sign up to set email alerts
|

Ortho-Substituted PCBs Kill Thymocytes

Abstract: The effects of exposure of acutely dissociated rat thymocytes to various polychlorinated biphenyl (PCB) congeners were examined using flow cytometry. Non-planar, ortho-substituted congeners caused a rapid cell death at low micromolar concentrations, while coplanar, dioxin-like congeners at the same concentration were without significant effect. The most potent of the congeners studied was PCB 52 (2,2',5,5'-tetrachlorobiphenyl), which had an IC50 of 3.96 microM at 20 min. Prior to loss of viability there was a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 41 publications
4
37
0
Order By: Relevance
“…The effects of the toxicants demonstrated in this report may partially be attributed to compromised membrane integrity. It has been demonstrated that ortho-substituted PCB congeners (but not coplanar congeners) alter calcium homeostasis by inducing changes in the integrity of mitochondrial and ER membranes which is accompanied by a decrease in mitochondrial membrane potential and accumulation of intracellular calcium [58]. It has also been shown that PCB 47 and PCB 52 (non-coplanar congeners; 10 lM) significantly compromised plasma membrane integrity concomitant with an accumulation of intracellular calcium [59].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of the toxicants demonstrated in this report may partially be attributed to compromised membrane integrity. It has been demonstrated that ortho-substituted PCB congeners (but not coplanar congeners) alter calcium homeostasis by inducing changes in the integrity of mitochondrial and ER membranes which is accompanied by a decrease in mitochondrial membrane potential and accumulation of intracellular calcium [58]. It has also been shown that PCB 47 and PCB 52 (non-coplanar congeners; 10 lM) significantly compromised plasma membrane integrity concomitant with an accumulation of intracellular calcium [59].…”
Section: Discussionmentioning
confidence: 99%
“…There have been many studies on the potential toxicity of substituted BPs in vivo [2,17,18] but very little work has been carried out on the evaluation of the molecular characteristics responsible for their toxicity and the mechanism of their interaction at a cellular and plasma membrane level. According to some studies, non-planar o-substituted BPs increased the cell membrane leakiness and decreased the membrane integrity compared to the planar BPs [17][18][19].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…There have been many studies on the potential toxicity of substituted BPs in vivo [2,17,18] but very little work has been carried out on the evaluation of the molecular characteristics responsible for their toxicity and the mechanism of their interaction at a cellular and plasma membrane level. According to some studies, non-planar o-substituted BPs increased the cell membrane leakiness and decreased the membrane integrity compared to the planar BPs [17][18][19]. While other studies have shown the non-planar o-substituted molecules to be less active compared to the planar p-substituted molecules because of the steric hindrance of the osubstituted species which influences their penetration into the phospholipid membrane [20][21][22].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…PCBs have been shown to have toxic effects on various organs including tissues of the nervous, reproductive, and immunologic systems (Buck et al 2000;Hennig et al 2002;Tan et al 2003Tan et al , 2004Bemis and Seegal 2004). In general, the toxicological effects of PCBs vary at the congener level (Safe 1992) and PCBs become more toxic with increasing chlorine content (Tanabe 1988).…”
Section: Introductionmentioning
confidence: 99%